Investigation of power-to-methanol processes coupling electrolytic hydrogen production and catalytic CO2 reduction. (2nd March 2016) - Rivera-Tinoco, R.; Farran, M.; Bouallou, C.; Auprêtre, F.; Valentin, S.; Millet, P.; Ngameni, J.R.
Abstract: The purpose of this research work is to perform the techno-economic assessment of a Power-to-MeOH technology that couples a model water eletrolyzer (either a polymer electrolyte or a solid oxide technology) with a model catalytic CO2 reactor. Simulations were made using ASPEN Plus V8.0. Regarding the SOEC/Methanol process, results of the simulation confirm the predominance of CAPEX on MeOH production cost. Cost reductions and lifespan improvement of SOEC technologies are found to be the major cost reduction drivers. Also, the speed at which the SOEC/Methanol facility is constructed is found to affect significantly the competitiveness of this process. Regarding the PEM/Methanol process, the cost breakdown analysis confirms the predominance of OPEX on the methanol cost, a value that is moderately impacted when the lifespan of the electrolyser is doubled. The energy efficiency of the electrolyser is therefore a key driver for a reduction of methanol production costs. Using state-of-the-art technologies, a methanol cost of 891 €/tonne was determined for the PEM/Methanol process and a methanol cost of 5459 €/tonne was determined for the SOEC/Methanol process. These costs represent respectively 2.5 and 15 times the current market price for methanol. However, promising methanol cost reductions are foreseeable by improving the water electrolysis technologies. Highlights: Methanol production coupled to two novel hydrogen production electrolysis process. Impact of electrolysis process on the competitiveness of methanol production. Competitiveness drivers are set for methanol process coupled to electrolysis.